Foreign player migration and athletic success in Greek football. Issue 3 (10th July 2017) - Travlos, Antonios K.; Dimitropoulos, Panagiotis; Panagiotopoulos, Stylianos
Abstract : Purpose: The purpose of this paper is to examine the migration of foreign football players that participated in the elite football championship in Greece and the impact of this migratory channel on the athletic success of the football clubs. Design/methodology/approach: The study analyzed a database of all migrant and local athletes that participated in the professional Greek football championship over the period 2001-2013 and performed descriptive and regression analyses. Findings: The regression analyses revealed a positive and significant statistical relation between the investment in foreign talents and the position of the clubs in the championship; however, this impact was more intense for foreign athletes after the formation of the Greek Super League (SL) in 2007 but on the contrary native athletes seem to contribute less to the athletic success than their foreign counterparts. Practical implications: The findings indicated that valuable resources where spent after SL formation for the acquisition of foreign well-trained athletes. Therefore, this study corroborated arguments in previous research that a basic reason for foreign player migration in football is the increased revenues accrued from the media and sponsors. The study also provided useful policy implications for football managers for improving their decisions on this matter. Originality/value: The present study fills a gap in the empirical literature and contributes significantly on the ongoing debate about the international athletes' migration and its impact on athletic success.